The Relationship between Fear of Missing Out (FoMO) and Self-Esteem in Middle Adolescents - Dewi, Erti Ikhtiarini; Fitria, Halena Laila; Kurniyawan, Enggal Hadi; Wuryaningsih, Emi Wuri; Erlando, Robby Prihadi Aulia (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2025)
Introduction: Middle adolescents are closer to their peers as part of their search for identity, so they are easily influenced by social trends, including the use of social media. High intensity of use can trigger fear of missing out (FoMO). FoMO encourages negative social comparisons that lead to decreased self-esteem, especially when adolescents feel that their lives are less ideal than others. This has an impact on the mental health, self-confidence, and social relations of adolescents. This study aims to determine the relationship between FoMO and self-esteem in middle adolescents at Senior High School 2 of Jember. Method: This research uses a correlational quantitative design with a cross-sectional approach. The sampling technique used was total sampling, totaling 1083 students. The instruments used were the FoMOs questionnaire and the Rosenberg Self-Esteem Scale (RSES). Data were analyzed univariately and bivariately with the Kendall Tau-c correlation test. Results: Bivariate analysis shows the value of ρ = 0.000 < 0.05, indicating a significant relationship between fear of missing out (FoMO) and self-esteem in middle adolescents at Senior High School 2 of Jember with a negative correlation direction. Conclusions: FoMO triggers a decrease in self-esteem in middle adolescents through upward social comparison of ideal content on social media. The important role of families, schools, and health workers, especially nurses, in helping teenagers manage stress due to FoMO, strengthen self-regulation, and increase self-esteem through digital education and emotional support.